Rare Site of Ectopic Pregnancy in a Patient with Bicornuate Uterus - Ayman Shehata; Mohamed El Namoury; Mostafa Heider (Case Reports in Obstetrics and Gynecology)
Ectopic pregnancy occurs in about 1-2% in normal cycles but in IVF cycles the rate jumps to 4%. No definite cause for ectopic pregnancy was detected, but many risk factors were described as abnormal tube, pelvic infection, or surgery. In this case report we found 2 abnormalities in eight-year infertile woman; the first abnormality was bicornuate uterus and the second abnormality was the site of ectopic pregnancy which was in between the two horns of uterus. ‎This is the only case reported with primary abdominal pregnancy with bicornuate uterus and both healthy ovaries and tubes.‎ The case was unstable and managed by laparotomy and repair of ectopic site after enucleation of sac using Vicryl 2/0. The case was discharged 24 hours after operation in good health.